2001
DOI: 10.1523/jneurosci.21-20-08043.2001
|View full text |Cite
|
Sign up to set email alerts
|

GABAB2 Is Essential for G-Protein Coupling of the GABAB Receptor Heterodimer

Abstract: GABA(B) receptors are unique among G-protein-coupled receptors (GPCRs) in their requirement for heterodimerization between two homologous subunits, GABA(B1) and GABA(B2), for functional expression. Whereas GABA(B1) is capable of binding receptor agonists and antagonists, the role of each GABA(B) subunit in receptor signaling is unknown. Here we identified amino acid residues within the second intracellular domain of GABA(B2) that are critical for the coupling of GABA(B) receptor heterodimers to their downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
125
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(141 citation statements)
references
References 38 publications
9
125
0
3
Order By: Relevance
“…The current model for the function of these dimers suggests that upon ligand binding, closure of the two lobes in only one of the two domains is sufficient to create a relative change in orientation between the two subunits, which in turn results in the activation of G-proteins (8). In the case of GABA B receptors, this model is consistent with the observations that only the GABA B R1 subunit is able to bind GABA B agonists or antagonists with measurable potency (5,6), that the GABA B R2 subunit is important for coupling to G-proteins (9,10), and * The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C.…”
supporting
confidence: 79%
“…The current model for the function of these dimers suggests that upon ligand binding, closure of the two lobes in only one of the two domains is sufficient to create a relative change in orientation between the two subunits, which in turn results in the activation of G-proteins (8). In the case of GABA B receptors, this model is consistent with the observations that only the GABA B R1 subunit is able to bind GABA B agonists or antagonists with measurable potency (5,6), that the GABA B R2 subunit is important for coupling to G-proteins (9,10), and * The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C.…”
supporting
confidence: 79%
“…This proposal then was demonstrated directly as we showed that CGP7930 acted as an agonist of HD2 expressed alone, demonstrating that this domain of the GABA B receptor behaved as a rhodopsin-like receptor. It is noteworthy that, even if CGP7930 could bind to the HD of GABA B1 , it would not induced G-protein activation, because we never observed any activation of the recombinant G-proteins by GABA B receptors lacking HD2 (17,19,20).…”
Section: Discussionmentioning
confidence: 76%
“…CGP7930 Activated GABA B2 in the Absence of GABA B1 -As mentioned above, GABA B2 possesses sufficient molecular determinants for G-protein activation (17)(18)(19)(20). Even when transfected alone, GABA B2 was expressed highly at the HEK293 cell surface (Fig.…”
Section: Cgp7930 Is a Positive Allostericmentioning
confidence: 77%
See 1 more Smart Citation
“…These receptors form dimers, but the GABA B receptor is an obligatory heterodimer constituted of the homologous GABA B1 and GABA B2 subunits (Jones et al, 1998;Kaupmann et al, 1998;White et al, 1998). GABA B1 is responsible for GABA recognition (Galvez et al, 2000a;Kniazeff et al, 2002), whereas GABA B2 is necessary for the correct trafficking of GABA B1 to the cell surface (Margeta-Mitrovic et al, 2000;Pagano et al, 2001) and is involved in G-protein activation (Galvez et al, 2001;Margeta-Mitrovic et al, 2001b;Robbins et al, 2001;Duthey et al, 2002).…”
Section: Introductionmentioning
confidence: 99%